The Influence of Customer Experience, Customer Service and Company Image on Customer Loyalty through Consumer Satisfaction as Intervening Variables - Singgih Andi Kurniawan; M. Arief (Journal of Business, Management, & Accounting, 2021)
This study aims to analyze the effect of consumer experience, service convenience and corporate image on customer loyalty through consumer satisfaction as an intervening variable performed on members Cooperative xxxmart Cibubur. This research is a survey research using a questionnaire as instrument and taken as many as 88 respondents who are members The XXX Martr Cooperative uses a simple random sampling method. Data collection is done by providing a list of questions to respondents use google form. This study uses analytical tools SmartPLS ver 3.0. The hypothesis is tested with path coefficients and indirect effects. The results of the study obtained the following conclusions; (1) Consumer experience (X1) has a significant effect on consumer satisfaction (Y1). (2) Convenience service (X2) has a significant effect on customer satisfaction (Y1). (3) Image company (X3) has no significant effect on customer satisfaction (Y1). (4) Consumer satisfaction (Y1) has a significant effect on customer loyalty (Y2). (5) Consumer experience (X1) has a significant effect on loyalty customers (Y2) either directly or through customer satisfaction (Y1). (6) Service convenience (X2) has a significant effect on customer loyalty (Y2) either directly or through consumer satisfaction (Y1). (7) Image company (X3) has no significant effect on customer loyalty (Y2) either directly or through consumer satisfaction (Y1). Satisfaction variable consumers (Y1) are able to mediate from the influence of experience variables consumer (X1) and service convenience (X2) on customer loyalty (Y2). However, the consumer satisfaction variable (Y1) failed to mediate the effect of corporate image variable (X3) on customer loyalty (Y2)